Intervertebral disc herniation in two coatis (Nasua nasua) and postoperative laminectomy membrane formation - Meyerhoff, Nina; Fehr, Michael; Neßler, Jasmin; Schütter, Alexandra Friederike; Dziallas, Peter; Molnár, Viktor; Ludwig, Carsten; Zabke, Sarah; Lehmbecker, Annika; Tipold, Andrea (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2018)
Magnetic resonance imaging revealed spinal cord compression due to intervertebral disc herniation of Hansen type I and II in the thoracolumbar vertebral column in two middle-aged coatis (Nasua nasua) with chronic progressive paraparesis. Surgical treatment included hemilaminectomy and partial corpectomy in one and dorsal laminectomy in the other coati. Both coatis recovered well after surgery. One showed unremarkable gait 6 and 15 months post surgery, while the other one suffered from recurrence of paraparesis leading to euthanasia because of deterioration of neurological signs 20 months after the first surgery. Necropsy revealed formation of a laminectomy membrane compressing the spinal cord. Histopathological signs of spinal cord injury and findings of degenerative processes in the intervertebral disc were comparable to those described in dogs. In conclusion, this case report shows for the first time that surgical intervention seems to be a useful and safe treatment in chronic intervertebral disc herniation in coatis, but relapses are possible.
Keywords: Myelopathy; paraparesis; ataxia; hemilaminectomy